UPAYA MENINGKATKAN EFISIENSI, PERAWATAN, DAN PEMELIHARAAN DRAINASE DUSUN RAWA INDAH - Syaifullah ihsan; Muhammad Fadil; Aridhotul Haqiyah (Universitas Islam 45 Bekasi, 2022)
Rawa Indah hamlet is one of the hamlets in Segaran Village, Karawang Regency which often experiences flooding due to poor drainage system, so it is necessary to handle drainage problems that occur in the hamlet. Based on the results of field observations, it was found that the main problem in the drainage of the Rawa Indah hamlet is the accumulation of garbage in the drainage channel which hampers drainage performance, so it is necessary to clean, handle, and maintain the channel so that the drainage system can work properly. Community service activities by conducting socialization and directing the implementation of activities, how to clean / reactivate / repair drainage channels, and how to determine the tools used to suit the needs. As a result of this activity, the community has learned how to activate or repair drainage channels so that drainage canals function normally.